Formation of Al3Sc in Al0.8Sc0.2 thin films. (June 2022) - Esteves, Giovanni; Bischoff, Joseph; Schmidt, Ethan W.S.; Rodriguez, Mark A.; Rosenberg, Samantha G.; Kotula, Paul G.
Abstract: The formation of Al3 Sc, in 100 nm Al0.8 Sc0.2 films, is found to be driven by exposure to high temperature through higher deposition temperature or annealing. High film resistivity was observed in films with lower deposition temperature that exhibited a lack of crystallinity, which is anticipated to cause more electron scattering. An increase in deposition temperature allows for the nucleation and growth of crystalline Al3 Sc regions that were verified by electron diffraction. The increase in crystallinity reduces electron scattering, which results in lower film resistivity. Annealing Al0.8 Sc0.2 films at 600 °C in an Ar vacuum environment also allows for the formation and recrystallization of Al3 Sc and Al and yields saturated resistivity values between 9.58 and 10.5 μΩ-cm regardless of sputter conditions. Al3 Sc was found to nucleate and grow in a random orientation when deposited on SiO2, and highly {111} textured when deposited on 100 nm Ti and AlN films that were used as template layers. The rocking curve of the Al3 Sc 111 reflection for the as-deposited films on Ti and AlN at 450 °C was 1.79° and 1.68°, respectively. Annealing the film deposited on the AlN template reduced the rocking curve substantially to 1.01° due to recrystallization of Al3 Sc and Al within the film. Graphical abstract: Image 1 Highlights: The formation of Al3 Sc is found to be driven by exposure to high temperatures. Low deposition temperatures lead to low crystallinity films with high resistivity. {111} textured Al3 Sc achieved by leveraging temperature and a template layer. Annealing Al0.8 Sc0.2 films reduces resistivity regardless of sputter conditions. Strong recrystallization effect seen in annealed films with {111} textured Al3 Sc.